Swimming angle and target strength of larval Japanese anchovy (Engraulis japonicus) - Ito, Yusuke; Yasuma, Hiroki; Masuda, Reiji; Minami, Kenji; Matsukura, Ryuichi; Morioka, Saho; Miyashita, Kazushi (Fisheries science, 2011)
The swimming angle of larval Japanese anchovy ( Engraulis japonicus ) was measured in a tank, and target strength (TS) was calculated using a theoretical scattering model. The mean swimming angle was 12.8° (SD ±22.1). Increased speeds of flow led to increased mean swimming angles. The mean swimming angle at flow of 5 cm s −1 was higher than at other speeds. TS values were estimated using a distorted-wave Born approximation model for two cases. Average values were 1–3 cm s −1 (11.5° ± 22.1) and 5 cm s −1 (16.6° ± 21.7) for cases 1 and 2, respectively. For case 1, TS ranged from −92.0 to −74.7 dB with a mean of −79.4 dB at 120 kHz. For case 2, TS ranged from −92.2 to −75.2 dB with a mean of −79.9 dB. The mean TS in case 2 was lower than that in case 1, with the maximum difference being 1.0 dB at 120 kHz (standard length 22.0 mm). However, there were no significant differences between the regression lines of cases 1 and 2. Thus, changes in flow speed altered the swimming angle of larval Japanese anchovy, but had little influence on TS.